An approach to determining the linkage between livelihood assets and the housing conditions in urban slums of Dhaka - Hanae Soma; Vibhas Sukhwani; Rajib Shaw (Journal of Urban Management, 2022)
In the backdrop of rapid urbanisation trends, the slum population has increased significantly in the fast-growing cities like Dhaka (the capital of Bangladesh). The increasing rural-to-urban migration, housing shortages, and the limited access to affordable housing, are recognised as some of the key underlying drivers of the same. Within the slum pockets, the households possess a varying level of livelihood assets which further determine their housing conditions. To establish a precise understanding of the linkages between the livelihood assets possessed by the slum households and their housing conditions, this study specifically focuses on the case of Dhaka. Building on the framework of sustainable livelihood analysis, and in reference to the World Bank's Urban Informal Settlements Survey 2016, a specific set of indicators are developed to assess the livelihood assets in different slum pockets of Dhaka and their linkage with the slum housing. Thereafter, correlation analysis of all household (secondary) data is conducted to derive broader findings, and an in-depth comparative analysis is conducted for two contrasting slum groups. Although the overall results do not reveal any direct linkage between the specific asset capitals and the housing conditions, the financial and natural capital are found to be the key factors in determining the level of livelihood assets. By comparing the locational characteristics, it is further found that the slums with highest level of livelihood assets are more located on the periphery of Dhaka city, while the contrasting slum groups are situated more in the central areas. Also, the comparison of housing conditions reveals that the households with higher level of livelihood assets have better access to durable and permanent alternatives for their housing structure. Although there is a huge scope of further research, it is hoped that the study findings will pave the pathway for enhancing slum housing conditions in Dhaka.
Keywords: 710; Dhaka; Housing conditions; Livelihood assets; Urban slums